Forming Civic Responsibility In Youth As A Condition For Improving Spiritual Collaboration - Berdikulov Chingiz Dusmuradovich (Global Scientific Publishing, 2025)
The article discusses the issue of forming civic responsibility in young people, which has become one of the main priorities of state policy. In this regard, the dependence of youth culture and behavior on achieving spiritual cooperation as an integral system in society is effectively highlighted. Also, the approach to the issue of forming civic responsibility in young people as a separate political-legal, moralspiritual phenomenon in the process of reforms is scientifically analyzed.
Keywords: Youth; responsibility; cooperation; behavior